URGENSI DAKWAH KYAI DALAM MENGAMBIL KEBIJAKAN UNTUK MENCIPTAKAN JEMBER RELIGIUS - Adwin Hakim Wali'ulhaq (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2021)
Kyai is someone who is an expert in Islam, both mastering the science of fiqh, monotheism and other religious sciences and has high personality integrity, has noble character and is influential in society. Kyai have many faces that reflect the complexity or diversity of the views of the kyai in politics. As an informal leader, the kiai is a person who is believed by the community to have enormous and charismatic authority. The focus of the problem in this study include the following: first, how is the urgency of the kyai's da'wah in making policies to create religious jember. secondly, what are the supporting factors and obstacles to the urgency of the kyai's da'wah in making policies to create a religious jember. The research method used is a qualitative approach with the type of descriptive research belonging to Cresswell which uses a purposive subject selection method and data collection techniques through observation, interviews and documentation. In analyzing the data the author uses data reduction, data presentation, and verification. The results of this study can be concluded that the urgency of the kyai's da'wah in taking policies to create religious jembers include: (1) Internal-personal by activating activities in taklim assemblies such as: mujahadah, and recitation of Tuesday pon, managing the Al-Qur'an Education Park , and the Commemoration of Islamic Holidays. (2) External-institutional by managing non-formal education, so that it is beneficial for development and closer social relations, and plays a role in the taklim assembly in the Jember community. (3) The Kyai's Da'wah Strategy is very significant, his da'wah activities are successful in teaching Islamic religious sciences from the various ways of da'wah that he does